2021
DOI: 10.1101/2021.04.18.440342
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Principles of mRNA targeting via the Arabidopsis m6A-binding protein ECT2

Abstract: Gene regulation dependent on N6-methyladenosine (m6A) in mRNA involves RNA-binding proteins that recognize m6A through a YTH domain. The Arabidopsis YTH-domain protein ECT2 is thought to influence mRNA 3′-end formation via binding to URU(m6A)Y sites, an unexpected conclusion given that ECT2 functions require its m6A binding activity, and that RR(m6A)CH is the m6A consensus site in all eukaryotes. Here, we apply the orthogonal techniques individual nucleotide-resolution UV-crosslinking and immunoprecipitation (… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 107 publications
(298 reference statements)
0
4
0
Order By: Relevance
“…Importantly, this allows target identification in very small numbers of cells and neurons without requiring biochemistry. TRIBE has been useful to a number of other labs working in different fields and model organisms ranging from humans to malaria parasites (Liu et al 2019;Alizzi et al 2020;Nguyen et al 2020;Arribas-Hernández et al 2021;Cheng et al 2021;Singh et al 2021;van Leeuwen et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, this allows target identification in very small numbers of cells and neurons without requiring biochemistry. TRIBE has been useful to a number of other labs working in different fields and model organisms ranging from humans to malaria parasites (Liu et al 2019;Alizzi et al 2020;Nguyen et al 2020;Arribas-Hernández et al 2021;Cheng et al 2021;Singh et al 2021;van Leeuwen et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these proteins containing the YTH domain in Arabidopsis all have the potential to bind m 6 A ( Wang et al., 2014 , 2015 ). ECT2 has been demonstrated to bind m 6 A-containing RNA directly in vitro and in vivo ( Scutenaire et al., 2018 ; Wei et al., 2018 ), and the binding sites of ECT2 to mRNA contain the plant-specific motif URUAY ( Wei et al., 2018 ) and the canonical site RRACH ( Arribas-Hernández et al., 2021a , 2021b ). Further genetic experiments showed that the functions of ECT2 are redundant with those of ECT3 and ECT4, suggesting that ECT3 and ECT4 are also m 6 A readers ( Arribas-Hernandez et al., 2018 , 2020 ).…”
Section: A Readersmentioning
confidence: 99%
“…However, we currently do not know how m 6 A machineries achieve selectivity toward certain motif sequences to accomplish m 6 A installation, removal and recognition. One likely scenario is that they may be localized to diverse sequence contexts through Regulation of m 6 A on mRNA metabolism in crops m 6 A possesses multiple regulatory effects on mRNA metabolism in Arabidopsis, such as mRNA stability (Anderson et al, 2018;Arribas-Hern andez et al, 2021b;Duan et al, 2017;Kramer et al, 2020;Shen et al, 2016;Wei et al, 2018), transcriptome integrity (Pontier et al, 2019), and alternative polyadenylation (Hou et al, 2021;Hu et al, 2021a;Parker et al, 2020;Song et al, 2021). Currently, substantial progresses have been made in deciphering the influence of m 6 A methylation on crop mRNA metabolism, mainly mRNA degradation and translation (Shao et al, 2021).…”
Section: Motifs In Cropsmentioning
confidence: 99%